Strengthening Religious Moderation Through Media of Traditional Cultural Arts Attractions in Tanjung - Kembarawan, I Gusti Komang (Jayapangus Press, 2023)
This study aims to examine the strengthening of the attitude of religious moderation implemented by the Sasak people who are Muslim and Hindu people who embrace Hinduism through the media of cultural arts. This research was designed in a qualitative descriptive manner using a case study model. The results of this study found three important findings related to the strengthening of religious moderation through art and culture media. First, there was cultural arts contact between the Sasak people and the Balinese people in the past which collaborated. Second, the arts collaboration that occurs is displayed in traditional, cultural, religious and important activities as a vehicle to enliven the event. Third, the arts and cultural expressions in activities, both informal and formal, have the opportunity to strengthen religious moderation.